2017
DOI: 10.1039/c7cp06412h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the inter-molecular charge transfer, second-order nonlinear optical and absorption spectra properties of a π-dimer under an external electric field

Abstract: In this work, we applied an external electric field (F) to a biphenalenyl derivative (BN-PLY) in the direction of the negative z-axis (F) and the positive z-axis (F), respectively. The influence of the two directions of F on the molecular structures and electronic properties is investigated, which gives interesting results. Density functional theory (DFT) calculations show that the application of F (F = 0 to -190 × 10) is an advantage toward improving π-dimer stability, which is attributed to an increase in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…M06-2X not only exhibits good performance for calculating electronic structures, but it is also broadly used to calculate electric properties, , that is, dipole moment, polarizability, and hyper-polarizabilities. In order to certify the reliability of M06-2X for calculating electronic contribution of the hyperpolarizabilities (β 0 ), Gu’s results display that the difference of β 0 values between MP2 and M06-2X is within 1.8% for C 6 F 6 H 6 (L), and therefore, M06-2X/6-311++G­(2d,2p) was chosen to calculate the β 0 values of alkalide L–M–L–M′ and superalkalide L–M–L–M 3 ′ O (M = Li and K, M′ = Li and Na).…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…M06-2X not only exhibits good performance for calculating electronic structures, but it is also broadly used to calculate electric properties, , that is, dipole moment, polarizability, and hyper-polarizabilities. In order to certify the reliability of M06-2X for calculating electronic contribution of the hyperpolarizabilities (β 0 ), Gu’s results display that the difference of β 0 values between MP2 and M06-2X is within 1.8% for C 6 F 6 H 6 (L), and therefore, M06-2X/6-311++G­(2d,2p) was chosen to calculate the β 0 values of alkalide L–M–L–M′ and superalkalide L–M–L–M 3 ′ O (M = Li and K, M′ = Li and Na).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Geometrical structures of these studied systems under different EEFs were fully optimized, and the frequency calculations confirmed that these geometrical structures lie on their minima of potential energy surfaces of ground states because frequency calculations display no imaginary values. M06-2X not only exhibits good performance for calculating electronic structures, but it is also broadly used to calculate electric properties, 55,56 that is, dipole moment, polarizability, and hyper-polarizabilities. In order to certify the reliability of M06-2X for calculating electronic contribution of the hyperpolarizabilities (β 0 ), Gu's results 47 display that the difference of β 0 values between MP2 and M06-2X is within 1.8% for C 6 F 6 H 6 (L), and therefore, M06-2X/6-311++G(2d,2p) was chosen to calculate the β 0 values of alkalide L−M−L−M′ and superalkalide L−M−L−M 3 ′O (M = Li and K, M′ = Li and Na).…”
Section: Computational Detailsmentioning
confidence: 99%
“…The first hyperpolarizability density and the natural transition orbital maps were also plotted by the Multiwfn. M06‐2X not only exhibits good performance for calculating electronic structures, but also broadly used to calculate electric properties,,, i.e . dipole moment, polarizability, hyperpolarizabilities.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In fact, a number of studies have revealed that E ex can effectively modify the electronic structures and transport properties of low‐dimensional systems . For examples, Song and co‐authors revealed a charge separation and further transport process under the influence of E ex in solar cell materials .…”
Section: Introductionmentioning
confidence: 99%
“…[59] Gao et al reported that the E ex with different directions and strengths could control the molecular structure, inter-molecular charge transfer and nonlinear optical properties of π-dimers. [60] Also, researchers have demonstrated that, an E ex can be utilized not only to influence the adsorption energy of small molecule but also to control the charge transfer between the small molecule and adsorbent. [61] Conceivably, E ex is one of the important elements that should not be ignored in the charge transfer process.…”
Section: Introductionmentioning
confidence: 99%